Analysis of the existence of PUD. Markets and Levies on Merchants' Welfare (Case Study of Petisah Market in Medan City) - Masnum Rambe; Maryam Batubara (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
PUD. is a market that sells various types of products in one area. Initially, the existence of PUD.s market has a positive impact in term of social and economic for market traders. However, currently it has a negative impact on the economy. The problem studied is how the existence of PUD is. Markets and levies on the welfare of traders at the Petisah Market in Medan. In this phenomenon, the authors are interested in researching the analysis of the existence of PUD. Markets and Levies on the Welfare of Petisah Market Traders. In this case the management of PUD. Markets and levies are very important to improve welfare in the division market, with the creation of a prosperous market many people prefer this market. This research method uses qualitative research methods, namely in the form of written or spoken words from people and actors that can be observed. This data was obtained from literature studies, interviews and observations to determine the existence of Medan city petisah market traders.